Wetland Ethnoscience Learning Resources: An Overview of Physical Science Concepts - Arif Sholahuddin; Muhammad Fuad Sya’ban; Rezky Fitriana; Amiratush Shalihah; Misbah Misbah (Universitas Lambung Mangkurat, 2022)
The potential of wetland ethnoscience in the South Kalimantan region needs to be explored more deeply so that it can be used as a learning resource that produces meaningful learning. This qualitative research has applied the Spradley method to explore the facts and experiences of wetland-based indigenous science in Amuntai Hulu Sungai Utara Regency to transform it into ethnoscience which is used as a natural science learning resource, especially for the concept of physical science. Ethnoscience learning resources for the Mamar Alabio village community in raising Alabio ducks have original knowledge in the form of hatching techniques and indigenous knowledge of the Banyu Hirang village community in the use of sunlight to dry water hyacinth and purun plants, as well as the use of a raw material pounder which were very potential as science learning resources related to with physics concepts according to the junior high school curriculum 2013. These ethnoscience learning resources can be integrated into science learning designs to produce meaningful learning and train students' competencies.